Multiplicity of Leucine Transport Systems in Escherichia coli K-12 - Rahmanian, Mohamad (1973)
The major component of leucine uptake in Escherichia coli K-12 is a common system for l-leucine, l-isoleucine, and l-valine (LIV-I) with a Michaelis constant (K(m)) value of 0.2 μM (LIV-I system). The LIV-binding protein appears to be associated with this system. It now appears that the LIV-I transport system and LIV-binding protein also serve for the entry of l-alanine, l-threonine, and possibly l-serine. A minor component of l-leucine entry occurs by a leucine-specific system (L-system) for which a specific leucine-binding protein has been isolated. A mutant has been obtained that shows increased levels of the LIV-I transport activity and increased levels of both of the binding proteins. Another mutant has been isolated that shows only a major increase in the levels of the leucine-specific transport system and the leucine-specific binding protein. A third binding protein that binds all three branched-chain amino acids but binds isoleucine preferentially has been identified. The relationship of the binding proteins to each other and to transport activity is discussed. A second general transport system (LIV-II system) with a K(m) value of 2 μM and a relatively low V(max) can be observed in E. coli. The LIV-II system is not sensitive to osmotic shock treatment nor to growth of cells in the presence of leucine. This high K(m) system, which is specific for the branched-chain amino acids, can be observed in membrane vesicle preparations.